The Influence of Communication and Motivation on Employee Spirit (Study at Aston Inn Hotel Tuban) - Widhya Pibriari, Ni Putu; Suthanaya, I Putu Bagus; Nugraha, Surya; Eli Sumerta, I Ketut (Akademi Komunitas MAPINDO, 2023)
This study aims to determine the effect of communication on the morale of the employees of the Aston Inn Hotel Tuban, to determine the effect of motivation on the morale of the employees of the Aston Inn Hotel Tuban, to determine the effect of communication and motivation on the morale of the employees of the Aston Inn Hotel Tuban, to determine the influence of communication and motivation on morale. Aston Inn Hotel Tuban employees work and know the independent variables that dominantly influence the work morale of the Aston Inn Hotel Tuban employees. In this study, the Aston Inn Hotel Tuban was used as the sample. The total number of employees is 80 people. The sampling technique in this study used the population method, namely the sampling method by taking all the number of employees so that the data is accurate for research purposes. The analysis technique used is regression analysis by testing the hypothesis using the F test and t test. The results showed that in the simultaneous analysis, it can be proven through the regression coefficients of Communication (b1) and Motivation (b2) on employee morale (Y) at the Aston Inn Hotel Tuban. If Communication (X1) and Motivation (X2) are increased by one point together, then employee morale (Y) will increase by 1.028 ( 0.440 + 0.588 ) points. This shows that Communication (X1) and Motivation (X2) have an effect on employee morale (Y) at the Aston Inn Hotel Tuban. This can be seen from the results of the simultaneous analysis which shows that Communication (X1) and Motivation (X2) have a positive effect on employee morale (Y). This was confirmed by using the F test to obtain Fcount = 26.826 > FTabel = 3.1154 with sig. F = 0.000 (p <0.05), so that a decision can be taken that the null hypothesis (H0) is rejected and accepts the alternative hypothesis (Ha), and has a significant effect. Keywords: Communication, Motivation, Morale.